Average Error: 0.0 → 0.0
Time: 16.1s
Precision: 64
$c11 \cdot x + c12 \cdot y$
$c12 \cdot y + x \cdot c11$
c11 \cdot x + c12 \cdot y
c12 \cdot y + x \cdot c11
double f(double c11, double x, double c12, double y) {
double r54714803 = c11;
double r54714804 = x;
double r54714805 = r54714803 * r54714804;
double r54714806 = c12;
double r54714807 = y;
double r54714808 = r54714806 * r54714807;
double r54714809 = r54714805 + r54714808;
return r54714809;
}


double f(double c11, double x, double c12, double y) {
double r54714810 = c12;
double r54714811 = y;
double r54714812 = r54714810 * r54714811;
double r54714813 = x;
double r54714814 = c11;
double r54714815 = r54714813 * r54714814;
double r54714816 = r54714812 + r54714815;
return r54714816;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.0

$c11 \cdot x + c12 \cdot y$
2. Final simplification0.0

$\leadsto c12 \cdot y + x \cdot c11$

# Reproduce

herbie shell --seed 1
(FPCore (c11 x c12 y)
:name "c11*x + c12*y"
(+ (* c11 x) (* c12 y)))